Morphological and genetic analysis of Ceratomyxa saurida Zhao et al. 2015 and Ceratomyxa mai sp. nov. (Myxozoa: Ceratomyxidae) from the East China Sea. Issue 1 (4th January 2023) - Yang, Chengzhong; Huang, Yanmei; Atkinson, Stephen D.; Bartholomew, Jerri L.; Ma, Honggang; Zhao, Yuanjun
Abstract : We describe Ceratomyxa saurida Zhao et al . 2015 and Ceratomyxa mai sp. nov. (Myxozoa: Ceratomyxidae) from the East China Sea. C. saurida was found in the gallbladders of 3/13 specimens of its type host, Saurida elongata Temminck and Schlegel 1846 (Aulopiformes). Myxospore characters were consistent with the original description to which we have added small subunit (SSU) rRNA gene data. C. mai sp. nov. was found in gallbladders of 3/13 specimens of S . elongata and 5/13 specimens of Neobythites sivicola Jordan and Snyder 1901 (Ophidiiformes). Mature myxospores of C. mai sp. nov. were crescentic in sutural view, with a deeply concave posterior angle 142.2±8.2° (125.8‒158.2°) and an arched anterior side. Shell valves were smooth and equal, 20.9±1.9 (17.3‒24.7) µm thick and 9.2±0.5 (8.1‒9.9) µm long, and joined at a straight, thin sutural plane passing between two nematocysts (polar capsules). The nematocysts were equal-sized, pyriform, 2.6±0.2 (2.4‒2.9) µm long and 2.7±0.2 (2.4‒3.3) µm wide, with their tapered ends pointed toward each other, located in the anterior third of the spore. Sequences of the SSU rRNA gene and internal transcribed spacer 1 showed that the isolates of C. mai sp. nov. obtained from S. elongata and N. sivicola were identical. The SSU rRNA gene sequence of C. mai sp. nov. was distinct from all known myxosporeans and clustered with C. saurida, and then with Ceratomyxa filamentosi Kalatzis, Kokkari and Katharios 2013, both of which also infect Aulopiformes fishes.